Using enhanced IDEF-SIM (EnIS) technique to model sustainable supply chains (SSCs) (Part II) - Hamzah, Halim Shah (2015)
A Sustainable Supply Chain (SSC) is a complex supply chain management system which follows the tenets of sustainable development and encompasses multiple interconnected business processes across all four product life phases – Pre Manufacturing, Manufacturing, Use, and Post Use. Using the Enhanced IDEF-SIM (EnIS) technique presented in the previous work, this study will demonstrate the modeling capabilities of the technique on the automotive industry. In order to demonstrate this new technique, the Sustainable Supply Chain for Vehicles (SSCV) will be used.